Adriaan Rademaker, Sophrosyne and the Rhetoric of Self-Restraint. Polysemy and Persuasive Use an Ancient Greek Value Term - Saravia de Grossi, María Inés (2007)
Fil: Saravia de Grossi, María Inés. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.